2002
DOI: 10.1111/j.1574-6941.2002.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nested PCR–DGGE (denaturing gradient gel electrophoresis) with group-specific 16S rRNA primers for the analysis of bacterial communities from different wastewater treatment plants

Abstract: The diversity of bacterial groups of activated sludge samples that received wastewater from four different types of industry was investigated by a nested PCR-DGGE (denaturing gradient gel electrophoresis) approach. Specific 16S rRNA primers were chosen for large bacterial groups (Bacteria and alpha-Proteobacteria in particular), which dominate activated sludge communities, as well as for actinomycetes, ammonium oxidisers and methanotrophs (types I and II). In addition primers for the new Acidobacterium kingdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(54 citation statements)
references
References 58 publications
1
53
0
Order By: Relevance
“…The number and abundance of bacterial species in the anaerobic digester is not exactly reflected by the number and intensity of the bands (Boon et al ., 2002). One bacterial species may demonstrate more than one band, one band may represent multiple species and species which have an abundance < 1% cannot be visualized by means of DGGE (Boon et al ., 2002), thus only dominant species were taken into account, which was the goal of this research. When interpreting these ecological parameters deducted from any molecular analysis, one should be aware of the limitations of the techniques used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number and abundance of bacterial species in the anaerobic digester is not exactly reflected by the number and intensity of the bands (Boon et al ., 2002). One bacterial species may demonstrate more than one band, one band may represent multiple species and species which have an abundance < 1% cannot be visualized by means of DGGE (Boon et al ., 2002), thus only dominant species were taken into account, which was the goal of this research. When interpreting these ecological parameters deducted from any molecular analysis, one should be aware of the limitations of the techniques used.…”
Section: Discussionmentioning
confidence: 99%
“…DGGE on the total bacterial community was performed following the PCR protocol of Boon and colleagues (2002), using the total bacterial primers P338f-GC and P518r (Muyzer et al ., 1993). The PCR was run with a 2720 thermal cycler (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…So far, only one report is available, which described the microbial community composition of PHAAOs in full-scale WWTPs operated in AO and A2O mode (47). However, the 16S rRNA gene-based clone library (58, 62), PCR-denaturing gradient gel electrophoresis (DGGE) (9), and quinone profiling (23, 26) analysis have revealed that the microbial community composition in full-scale WWTPs operated in AO or A2O mode differed from that in fully aerobic mode; therefore, we investigated the microbial community compositions of PHAAOs in full-scale WWTPs operated in fully aerobic mode, the most common configuration mode of activated sludge processes throughout the world.…”
Section: Discussionmentioning
confidence: 99%
“…Heuer and Smalla (1997) used Actinomycete specific primers to monitor Actinomycete communities in the potato rhizosphere. Similarly Boon et al (2001) used several group specific nested PCR systems to identify a lot of groups under same DGGE conditions. So the need of group specific primers is there to find out the diversity and identity of the members of a specific group.…”
Section: Discussionmentioning
confidence: 99%